Generation of a Q-Switched Erbium-Doped Fiber Laser using MXene V₂CTx as Saturable Absorber - Abdul Ghafar , Nurul Athirah Mohamad; Markom, Arni Munira; Zulkipli, Nur Farhanah; Apsari, Retna; Harun, Sulaiman Wadi (Semarak International Journal of Electronic System Engineering, 2025)
Fiber laser generation is widely studied for applications in telecommunications and industrial processes, yet enhancing laser performance, especially with effective saturable absorbers (SAs), remains a challenge. This research focuses on using MXene V₂CTx film as a saturable absorber to generate Q-switched fiber lasers. A passive fiber laser was developed using a solution casting method to fabricate the MXene V₂CTx SA. When pump power was increased from 50.66 to 149.79 mW, stable Q-switched pulses at 1530 nm were achieved, with a maximum repetition rate of 93.41 kHz, a pulse width of 3.24 µs, and a pulse energy of 48.82 nJ. These findings demonstrate that MXene V₂CTx is effective in producing stable Q-switched fiber lasers, offering potential for enhanced laser performance in various applications.